Efikasi Campuran Herbisida Pendimethalin serta Pengaruhnya Terhadap Gulma dan Hasil Tanaman Kedelai - M. Ilyas Abubakar; Hasanuddin Hasanuddin; Muhammad Rusdi; Haswandi Haswandi (Jurnal Agrista, 2006)
The Efficacy of Pendimethalin Herbicide Mixtures and its Effects on Weed and Yield of SoybeanABSTRACT. Field research has been conducted in Experimental Farm of Agriculture Faculty University of Syiah Kuala Banda Aceh from March to July 2006 for evaluation efficacy of pendimethalin herbicide mixtures and its effect on weed and yield of soybean. Pendimethalin+imazetaphyr herbicide at dosage of 1.0 kg+70 g.a.i. ha-1 could decrease dry weight weed and increase percentage of weed control. Dried seed yield were higher when pendimethalin+imazetaphyr herbicide was applied at dosage 1.0 kg + 70 g.a.i. ha-1.